O megalitismo do concelho de Mora (Portugal): Da investigação à criação do Museu Interativo do Megalitismo - Rocha, Leonor (2021)
The importance of the megalithic ensemble existing in the municipality of Mora has been known internationally since 1921, through the publication of one of the first monographs dedicated to Prehistory in Portugal, the “El Neolítico de Pavia” (Correia, 1921). The recognition of the value of its cultural heritage led the municipality to invest in a systematic program to support research projects since 1994, coordinated by the signatory and, at the beginning of the second decade of the 21st century, to move towards a project to disseminate this heritage, through the creation of a museum dedicated to megalithism. The Interactive Museum of Megalithism in Mora is a museum that combines the more traditional view of museology with new interactive trends and aims to be an option of high cultural quality, for a tour in the interior of the country.